Perceptions of language (mis)fit at a multilingual workplace : the case of the University of Vaasa - Järlström, Maria; Piekkari, Rebecca; Pilke, Nina; Turpeinen, Hanna (Palgrave Macmillan, Cham, 2020)
Based on a case study we identify sources and contexts of linguistic challenges that academic and university services staff perceive at a multilingual workplace. Some of these challenges produce subjective perceptions of language misfit—a concept that refers to a sense of inadequacy in the social context through which professionals communicate specialized knowledge. Professionals who experience misfit have limited language skills or their skills are inconsistent with the language policies and practices of the university and/or the region where the university is embedded. Our findings suggest that language misfit and fit form a dualistic pair of concepts which is dynamic and context-specific. We offer a contribution to person-environment (mis)fit research and the study of multilingual organizations, which has to date focused on private, for-profit organizations.
Keywords: languages; multilingualism; language skills; language policy; English language; change; communication; use of language; tertiary education; learning; fi=Johtaminen ja organisaatiot|en=Management and Organization|